Look again : the power of noticing what was always there - Sharot, Tali; Sunstein, Cass R. (One Signal Publishers, Atria, 2024)
A neuroscience professor and a Harvard law professor team up in this groundbreaking work, based on decades of research in the psychological and biological sciences, that shows how disrupting our routines can lead to seeing, feeling and noticing again--and embracing much-needed change to live happier, more fulfilling lives.